Pemanfaatan Ampas Sagu sebagai Mulsa Organik dalam Peningkatkan Pertumbuhan Tanaman Sagu (Metroxylon sagu Rottb.) Di Lapang - Mikhael Sada; Florentina Heningtyas Listyorini; Barahima Abbas (Cassowary, 2021)
Sago palm need to be cultivated intensively for increasing carbohydrate resources to anticipate the deficiency of energy sources of the world. This study aims to measure the influences of sago dregs to the sag palm growth in the field. The experimental method used in this works was Randomized Block Design that consisting of five treatments sago dregs weights in the russet stages of sago palm. The composition of the treatment is follows: without sago dregs (P0), 5 kg sago dregs tree-1 (P1), 10 kg of sago dregs tree-1 (P2), 15 kg sago dregs tree-1 (P3), 20 kg sago dregs tree-1 (P4). The results showed that sago dregs had a significant effect of the spear leaves growth, but not significantly effect of the plant height growth, number of leaflets growth, and number of leaflets. Utilization of 10 kg sago dregs tree-1 as mulch was calculated influence of the spear leaf growth and utilization of 20 kg sago dregs as mulch inhibitory of sago palm growth.